dFRAME: A Video Recording-Based Analytical Method for Studying Feeding Rhythm in Drosophila - Niu, Mengxia; Zhang, Xiaohang; Li, Weihan; Wang, Jianxun; Li, Yan (Frontiers in Genetics, 2021)
Animals, from insects to human, exhibit obvious diurnal rhythmicity of feeding behavior. Serving as a genetic animal model, Drosophila has been reported to display feeding rhythms; however, related investigations are limited due to the lack of suitable and practical methods. Here, we present a video recording-based analytical method, namely Drosophila Feeding Rhythm Analysis Method, dFRAME. Using our newly developed computer program, FlyFeeding, we extracted the movement track of individual flies and characterized their food approaching behavior. To distinguish feeding and no-feeding events, we utilized high-magnification video recording to optimize our method by setting cut-off thresholds to eliminate the interference of no-feeding events. Furthermore, we verified that this method is applicable to both female and male flies and for all periods of the day. Using this method, we analyzed long-term feeding status of wild-type and period mutant flies. The results recaptured previously reported feeding rhythms, and revealed detailed profiles of feeding patterns in these flies under either light/dark cycles or constant dark environments. Together, our dFRAME method enables long-term, stable, reliable, and subtle analysis of feeding behavior in Drosophila. High-throughput studies in this powerful genetic animal model will gain great insights into the molecular and neural mechanisms of feeding rhythms.